Anisotropic Thermal Conductive Composite by the Guided Assembly of Boron Nitride Nanosheets for Flexible and Stretchable Electronics. (18th June 2019) - Hong, Haeleen; Jung, Yei Hwan; Lee, Ju Seung; Jeong, Chanho; Kim, Jong Uk; Lee, Sori; Ryu, Hyewon; Kim, Heyn; Ma, Zhenqiang; Kim, Tae‐il
Abstract: Owing to the growing demand for highly integrated electronics, anisotropic heat dissipation of thermal management material is a challenging and promising technique. Moreover, to satisfy the needs for advancing flexible and stretchable electronic devices, maintaining high thermal conductivity during the deformation of electronic materials is at issue. Presented here is an effective assembly technique to realize a continuous array of boron nitride (BN) nanosheets on tetrahedral structures, creating 3D thermal paths for anisotropic dissipation integrated with deformable electronics. The tetrahedral structures, with a fancy wavy shaped cross‐section, guarantee flexibility and stretchability, without the degradation of thermal conductivity during the deformation of the composite film. The structured BN layer in the composites induces a high thermal conductivity of 1.15 W m −1 K −1 in the through‐plane and 11.05 W m −1 K −1 in the in‐plane direction at the low BN fraction of 16 wt%, which represent 145% and 83% increases over the randomly mixing method, respectively. Furthermore, this structured BN composite maintains thermal dissipation property with 50% strain of the original length of composite. Various electronic device demonstrations provide exceptional heat dissipation capabilities, including thin film silicon transistor and light‐emitting diode on flexible and stretchable composite, respectively. Abstract : The reported anisotropic thermal conductive composite film can serve as a flexible and stretchable heat sink for high‐performance electronics. The assembled BN layer on the tetrahedral structure in composite guarantees anisotropic heat dissipation and flexibility and stretchability without degradation of thermal conductivity during the deformation of devices, overcoming the otherwise unsolvable trade‐off of high thermal conductivity against mechanical stability.